Implementasi Pendidikan Antikorupsi dalam Menumbuhkan Sikap Integritas Peserta Didik di MA MA’ARIF Cepogo Boyolali - Putri, Indah Agustina; Nugroho, Jagad Agung; Budiyono, Indra; Prasetyo, Aris Budi (Universitas Pahlawan Tuanku Tambusai, 2026)
Socialization activities regarding the Implementation of Anti-Corruption Education in Cultivating Students' Integrity Attitudes have been carried out at MA'Ma Arif Cepogo, Boyolali Regency. Corruption is a serious threat to national development that requires early prevention efforts through Education. This socialization activity was carried out on November 15, 2025, involving grade XII students, using pretest, material delivery, and posttest methods. The socialization material includes the concept of anti-corruption, instilling anti-corruption values, and their application in the school environment. The results of this activity prove an increase in students' understanding of the concept of anti-corruption supported by the activeness and participation of teachers and students. Anti-corruption education in schools is an effective strategy for character formation in students with integrity. Through internalization of the values of honesty, responsibility, discipline, and hard work, it is hoped that students can apply anti-corruption principles in everyday life and contribute to efforts to eradicate corruption in the future.